Produção de forragem e valor nutritivo de pastos de capim elefante sob manejo convencional e orgânico - Simonetti, Gabriela Descovi (2017)
The objective of this research was to evaluate the forage yield and nutritive value of elephantgrass on conventional and organic systems. In the organic system, species with complementary growth periods were combined; elephantgrass was planted in lines 3m apart from each other; between the rows of elephantgrass, during the winter period, ryegrass was sown and in the summer period the development of species of spontaneous growth was allowed. In the conventional production, two pastures were studied, one with the same strategy of organic production, but with chemical fertilization and another with elephantgrass cultivated alone. 100 kg of N ha-1 were applied with mineral and organic fertilization (bovine manure and pig slurry) in conventional and organic systems, respectively. Holstein cows receiving 0.9% of body weight complementary concentrate feed were used in the evaluation. The experimental design was completely randomized, with three treatments (forage systems), three repetitions (paddocks) and with repeated measures in time (seasons). Forage mass parameters of pre and post grazing, botanical composition, forage production and nutritive value were evaluated. Forage samples were collected by hand-plucking technique for the determination of organic matter, crude protein and in situ digestibility of organic matter. During the experimental period (337 days) seven grazing cycles were performed. Forage production and stocking rate were 12548; 10270; 19168 kg ha-1 and 3.3; 2.1; 4.5 AU ha-1 dia-1, respectively, for the forage systems. Pastures mixed, on conventional and organic production, present best forage distribution throughout the seasons. Higher value of forage production was observed in elephantgrass cultivated alone, on conventional system. Better value of nutritional value parameters were observed in organic pasture.